Pengaruh Terpaan Media TikTok dan Kampanye #CreatorContribution @Pandawaragroup terhadap Perilaku Peduli Lingkungan Pengikut - Sabar Ernesto Sanchez Simamora; Widyo Nugroho (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
This study aims to determine whether there is an effect of tiktok media exposure and the #creatorcontribution campaign on followers' environmental care behavior, and the theory used in this study is Social Cognitive Theory. The research method used in this research is the Quantitative method, by collecting data through a survey using a questionnaire filled out by randomly selected respondents. by distributing questionnaires to respondents who are followers of the Tiktok Pandawaragroup account, a minimum of 400 respondents were obtained which were calculated using the slovin formula, which was then processed using SPSS version 25. The results of the research obtained from 400 respondents show that there is a very strong influence between Tiktok Media Exposure and the #creatorcontribution Campaign made by Pandawara Group on the Environmental Care Behavior of its Followers, the results of the study indicate that there is an influence on Tiktok media exposure and the #creatorcontribution campaign from the Tiktok @pandawaragroup account has an influence on the environmental care behavior of its followers.